L’école chinoise à travers les statistiques : la catégorisation ethnique et résidentielle en question - Lijuan Wang (Recherches en Éducation)
China has inherited from its past statistical categories based on ethnicity (Han/shaoshu minzu or minorities) and residency (hukou system). We study the issues resulting from this categorization, especially concerning education and schooling.The common practice and the lack of homogeneity of the current filing system raise a problem, because the essentialisation of ethnical and residential categories have uncertain scientific basis. Nowadays, this filing system is subject of critics shared by Chinese sociologists who are in search of a new and better form of classification that captures the reality of contemporary China (Rocca, 2008). The difficulty to obtain complete or relevant statistical sources lead us to use in our survey a filling system more focused on sociological than political concepts. Our research concerns four secondary schools in Xichang, capital city of Liangshan Yi Prefecture (Sichuan). And it reveals the complexity of the educational reality in this country, beyond the categories of the common political practices (minority membership, residential status).